2018
DOI: 10.1038/s41598-018-29135-w
|View full text |Cite|
|
Sign up to set email alerts
|

Intradermal immunization by Ebola virus GP subunit vaccines using microneedle patches protects mice against lethal EBOV challenge

Abstract: Development of a safe and efficacious filovirus vaccine is of high importance to public health. In this study, we compared immune responses induced by Ebola virus (EBOV) glycoprotein (GP) subunit vaccines via intradermal immunization with microneedle (MN) patches and the conventional intramuscular (IM) injection in mice, which showed that MN delivery of GP induced higher levels and longer lasting antibody responses against GP than IM injection. Further, we found that EBOV GP in formulation with a saponin-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
(58 reference statements)
0
28
0
Order By: Relevance
“…Coated and dissolvable MNs represent dry formulations, which compared to liquid-based injectable vaccines are easier to store, require lesser space and weight capacity for storage, and have reduced cost of transport. Such designs have been developed for viruses including influenza, 22,[26][27][28][29][30][31][32][33][34][35][36][37] hepatitis B, [38][39][40][41] hepatitis C, 42 polio, 43,44 herpes simplex, 45,46 human papillomavirus, 47,48 rotavirus, 49 measles and rubella, 50-52 rabies, 53 HIV, 54,55 Ebola, 56 chikungunya, and West Nile virus. 57 However despite extensive advances in MN-based vaccines, there are limited studies addressing the delivery of LAVs.…”
Section: Resultsmentioning
confidence: 99%
“…Coated and dissolvable MNs represent dry formulations, which compared to liquid-based injectable vaccines are easier to store, require lesser space and weight capacity for storage, and have reduced cost of transport. Such designs have been developed for viruses including influenza, 22,[26][27][28][29][30][31][32][33][34][35][36][37] hepatitis B, [38][39][40][41] hepatitis C, 42 polio, 43,44 herpes simplex, 45,46 human papillomavirus, 47,48 rotavirus, 49 measles and rubella, 50-52 rabies, 53 HIV, 54,55 Ebola, 56 chikungunya, and West Nile virus. 57 However despite extensive advances in MN-based vaccines, there are limited studies addressing the delivery of LAVs.…”
Section: Resultsmentioning
confidence: 99%
“…The same authors also used the CMC‐coated microneedles to deliver H1N1 virus‐like nanoparticles . CMC coatings have also been used to deliver vaccines against the measles (caused by the Rubeola virus), human papillomavirus pseudovirus (HPV16), human orthopneumovirus, Hepatitis B, rotavirus, and Ebola . In 2014, Prausnitz and co‐workers showed that CMC does not have direct immunogenic effects and could protect against a lethal influenza challenge .…”
Section: Macroscale Materials For Immunotherapymentioning
confidence: 99%
“…We found that the SBLP were immunogenic, especially in promoting Th1-and Th2-type immune responses. However, some studies have shown that immunization with unadjuvanted GP nanoparticle vaccines by intramuscular (IM) injection induces IgG1 antibodies but not IgG2a antibodies against GP [27,34,35]. Therefore, we assumed that this outcome might be related to the presence of GEM particles, which can induce Th1-type immune responses when used as a vaccine adjuvant [36][37][38].…”
Section: Discussionmentioning
confidence: 98%
“…The neutralizing activity of sera from vaccinated mice against pseudoviruses containing an SUDV GP, based on a human immunodeficiency virus backbone, was analyzed as described in previous studies [27]. Briefly, diluted serum samples were added to Huh7 cells, followed by the addition of 100× 50% tissue-culture infective dose (TCID 50 ) of pseudotype virus (prepared in a volume equal to that of the serum samples), which were incubated at 37 • C for 1 h before addition to the Huh7 cells.…”
Section: Pseudovirion Neutralization Assaymentioning
confidence: 99%